Mathematical Modeling of Hydrodynamic and Heat Transfer in a Two-Phase Thermosyphon; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Nee A. E. Aleksandr Eduardovich (2016, 2016)
Title screen